PENGEMBANGAN MEDIA KALENDER HURUF DAN ANGKA UNTUK MENGENALKAN HURUF-HURUF ABJAD DAN ANGKA PADA ANAK USIA 5-6 TAHUN - dwi imam efendi (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2021)
This research produces a specific product and tests the product. iThe product developed will be tested and each trial will be evaluated. The ASSURE model combines iall instructional activities, starting from designing good activities starting with student interest then presenting new material. The conclusions obtained from this research and development are as follows: Media development Media calendar letters and numbers in learning have been validated by several experts. Media experts get a percentage of 90%, material experts get a percentage of 92%, so that the letter and number calendar media in learning is declared very feasible to use. So that the letter and number calendar media in thematic learning is very much needed and contributes greatly to supporting learning.